Governance and Its Role in Reducing Corruption in Commercial Companies - MEDJDOUB, Nawal (Journal of Human Sciences, 2025)
Adopting corporate governance is an important requirement as a mechanism to reduce corruption affecting commercial companies, as the advancement of the business sector necessarily requires the effective implementation of accountability, transparency, justice, and equality. The adoption of governance ensures the regulation of corporate crimes through internal and external oversight. Undoubtedly, the adoption of governance protects the rights and interests of minorities in commercial companies from the tyranny of the majority, all to achieve the objectives for which the company as a legal entity was established.